Answer:
0.38 m
Explanation:
As we know that the person due to the airbag action, comes to a complete stop, in a time of 36 msec or less, and during this interval, is decelerated at a constant rate of 60 g, we can find the initial velocity (when airbag starts to work), as follows:
vf = vā -a*t Ā
If vf = 0, we can solve for vā:
vā = a*t = 60*9.8 m/s²*36*10ā»Ā³s = 21.2 m/s
With these values of vā, a and t, we can find Īx, applying any kinematic equation that relates these parameters with the displacement.
Just for simplicity, we can use the following equation:
Ā [tex]vf^{2} - vo^{2} =2*a*d[/tex]
where vf=0, vā =21.2 m/s and a= -588 m/s².
Solving for d:
Ā [tex]d =\frac{21.2 m/s}{588 m/s2} = 0.38 m[/tex]
ā d = 0.38 m